Pendampingan Penyuluhan Kesehatan Ibu dan Anak di Posyandu Anggrek Desa Sukmajaya - Nur Azhima; Hari Rahman; Tinta Ilmiati; Siti Aminah; Siti Lutfi Latifah; Asni Aulia Nurchalizah; Siti Rifatul Mahmudah; Putri Humeiroh; Farhana Tuahena (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The assistance of maternal and child health counseling at the Anggrek Posyandu, Sukmajaya Village aims to increase public knowledge and awareness regarding the importance of maternal and child health, especially in terms of providing vitamin A, measuring the growth of infants and toddlers, and early detection of health problems in children. This activity involved midwives, posyandu cadres, and KKN students as facilitators in counseling and practicing measuring weight, height, and head circumference of babies, as well as distributing vitamin A. The counseling used lecture, discussion, and demonstration methods. The parties involved in this activity included village midwives, posyandu cadres, mothers from the community, and KKN laa roiba female students. The results of this activity showed an increase in mothers' knowledge regarding the importance of monitoring child growth and providing vitamin A. Although there were technical challenges in the measurement process, such as difficulty in calming children during the examination, this activity was able to achieve the expected goals. The program evaluation showed the need for improved technical coordination and the addition of tools in the implementation of posyandu activities in the future. Keywords: health education, mentoring, vitamin A, child growth, integrated health posts, maternal and child health.